1) k^2 + 8k + 12 = 0
2) a^2  2a  48 = 0
3) x^2 + 12x + 20 =0
4) m^2  12m + 26 = 0
5) p^2  8p +21 = 6
6) a^2  2a  8 = 0
2) a^2  2a  48 = 0
3) x^2 + 12x + 20 =0
4) m^2  12m + 26 = 0
5) p^2  8p +21 = 6
6) a^2  2a  8 = 0

Half the middle term in this case 8k/2 is 4k
then 4 goes into the brackets, 4^2 is 16 and we need it to equal 12 so outside the brackets put 4
(k+4)^24=0
From this then rearrange the formula to equal k
(k+4)^2=4
k+4=+/2
k= 2 and k=6
EDIT to check you can substitute k= 2 back into the equation
(2)^2+8(2)+12 = 0
2) (a1)^249=0
(a1)^2=49
a1=+/7
a=8 and 6
8^22(8)18=0
3) (x+6)^24=0
(x+6)^2=4
x+6=+/2
x=4 and 8
From this you should be able to get the general gist of it if you don't just message me.
then 4 goes into the brackets, 4^2 is 16 and we need it to equal 12 so outside the brackets put 4
(k+4)^24=0
From this then rearrange the formula to equal k
(k+4)^2=4
k+4=+/2
k= 2 and k=6
EDIT to check you can substitute k= 2 back into the equation
(2)^2+8(2)+12 = 0
2) (a1)^249=0
(a1)^2=49
a1=+/7
a=8 and 6
8^22(8)18=0
3) (x+6)^24=0
(x+6)^2=4
x+6=+/2
x=4 and 8
From this you should be able to get the general gist of it if you don't just message me.

1. k^2 + 8k +12= 0 what two numbers multipy to be 12 but add to be 8 (6,2)
(k+6)(k+2)=0
k=6
k=2
Check answer 2^2 + 8(2)+ 12 =0 ==> 416+12=0 and 6^2=8(6)+12 = 3648+12= 0 cks
2. (x6)(x8) x=6,8
3. (x+10)(x+2) x=2,10
4 did you write 4 wrong
5.p^28p+15=0
(p5)(p3)=0 p=3,5 ck 3^28(3)+15 = 924+15 = 0 ck 2540=15 = 0 ck
6 (a4)(a++)=0 a=4,2 ck 1688=0 ck and 4+48 =0 ck
(k+6)(k+2)=0
k=6
k=2
Check answer 2^2 + 8(2)+ 12 =0 ==> 416+12=0 and 6^2=8(6)+12 = 3648+12= 0 cks
2. (x6)(x8) x=6,8
3. (x+10)(x+2) x=2,10
4 did you write 4 wrong
5.p^28p+15=0
(p5)(p3)=0 p=3,5 ck 3^28(3)+15 = 924+15 = 0 ck 2540=15 = 0 ck
6 (a4)(a++)=0 a=4,2 ck 1688=0 ck and 4+48 =0 ck

1. k = 2,6
2. a = 8, 6
3. x = 2, 10
4. m = sqrt.(10) + 6,  sqrt.(10) + 6
5. p = 5, 3
6. a = 4,  2
2. a = 8, 6
3. x = 2, 10
4. m = sqrt.(10) + 6,  sqrt.(10) + 6
5. p = 5, 3
6. a = 4,  2